Pemikiran Teologi Pendidikan Kristian Robert Raikers - Siska Wira Sasmitha; Midtra Yhera; Silva Silva; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the theological thought of Christian education by Robert Raikes as the pioneer of Sunday School within its historical context and its contribution to the development of Christian education. The purpose of this research is to reveal the theological background and motivations behind Raikes' initiation of church-based education and its impact on society and the church today. The method used is a literature study with a descriptive qualitative approach, analyzing historical and theological sources. The findings show that Raikes had a deep concern for the social and moral condition of poor children in 18th century England, which led him to establish Sunday Schools as a means of religious and character education. Raikes' educational thoughts and practices became a crucial foundation for the development of modern Christian education. The implication of this research is the need for today’s churches and Christian educational institutions to emulate Raikes' spirit of service and social concern in delivering transformative education.